Preparation of Nano-Ag-TiO2 Composites by Co-60 Gamma Irradiation to Enhance the Photocurrent of Dye-Sensitized Solar Cells - Le Thanh Nguyen Huynh; Viet Hai Le; Thanh Long Vo; Thi Kim Lan Nguyen; Quoc Hien Nguyen; Thai Hoang Nguyen (International Journal of Photoenergy)
Nano-silver-titanium dioxide (Ag-TiO2) composites were prepared from commercial TiO2 (P25, Degussa) and silver nitrate (AgNO3) by gamma Co-60 irradiation method with various initial concentrations of AgNO3. The nano-AgTiO2 composites are utilized as the photoanode for dye-sensitized solar cells (DSCs). Under full sunlight illumination (1000 W/m2, AM 1.5), the efficiency of DSCs has improved significantly despite the Ag content of below 1%. The DSC—assembled with 0.75 Ag-TiO2 (0.75% Ag) photoanode—showed that the photocurrent was significantly enhanced from 8.1 mA.cm−2 to 9.5 mA.cm−2 compared to the DSCs using bared TiO2 photoanode. The unchanged open-circuit voltage resulted in the overall energy conversion efficiency to be increased by 25% from 3.75% to 4.86%. Electrochemical impedance spectroscopy (EIS) analysis showed that the charge transfer resistance is reduced when increasing Ag content, demonstrating that the charge transfer at TiO2/dye interface was enhanced in the presence of silver nanoparticles.